International Trade with Special Emphasis on the Free Movement of Goods and Services in Kosovo and Beyond - Vlahna, Dafina; Kuçi, Hajredin; Kuçi, Argona; Vlahna, Kastriote (Frontiers in Law, 2024)
Current topic in international countries and especially in the member countries of the European Union is free trade, with special emphasis on the freedom of circulation of goods. Based on the legislation in force and the developed practice when it comes to the markets developed between international states, the study in question analyses the specific problems that appear in the markets developed between the individual states of the EU member states. Thus, based on the past and today, the fundamental value of the EU is trade, especially the trade of goods between EU member states, for which special importance has been given in the international legislation concretized for the UN member states. and also, of the EU organization. Thus, based on the past and today, when we focus on free markets, especially trade in goods, it can be seen that EU member states used to have major barriers to trade in goods, while now they have decreased significantly, with some exceptions in the sector of agriculture. More specifically, the member states of the EU organization, with the mandatory observance of the rules set for free trade, are in their favor since, based on the statistics of the past years, tariffs on the import and export of goods have been reduced, and also even in most cases for certain goods the tariffs are completely excluded. In addition to the international states based on the state of Kosovo, from the research done we can say that the state of Kosovo, even though it is not a member state of the UN Organization or the EU, still stands well in terms of free trade of goods, this is due to the fact that free trade agreements have been signed with the countries of the region, a concrete case recently is the agreement with the state of Albania and also the free trade agreement with the countries of Central Europe. Thus, we can say that this study of this paper presents the latest developments related to international free trade with special emphasis on the goods market and analyses the possible economic and political results of international countries.